STRUKTUR PASAR DAN PERILAKU INDUSTRI SEMEN DI INDONESIA TAHUN 2004-2005 - Seniono Nugroho; Sri Susilo (Journal of Indonesian Economy and Business (JIEB), 2007)
The purpose of this research is to know and analyze the market structure and cement industry behavior in Indonesia year 2004-2005. Data utilized is primary and secondary data. Primary data are compiled through field survey, while secondary data are based on data from Indonesian Cement Association, “Warta Semen dan Beton Indonesia”, and “CIC Indocommercial”. The analysis instrument to determine the market structure is CRn (Concentration Ratio n) and Hirchman-Herfindahl Index (HHI). Then, descriptive analysis is utilized to analyze the cement industry behavior.Based on ratio concentration method approach of four enterprises with highest market segment (CR4), the market structure in the cement industry in Indonesia year 2004 and 2005 are classified as concentrated oligopoly, and oligopoly type 1 or full oligopoly classification is fulfilled on ratio concentration method for the eight enterprises with highest market segment (CR8) in 2004. Based on Hirchman-Herfindahl Index method, the cement industry in Indonesia year 2004-2005 are classified as concentrated. Industry conduct based on strategy to compete using strategy to compete with price and non-price include the product development, promotion or advertising of product, and product distribution.